Effect of Differente Manmres Supplemen on the Grey Oyster Mushroom (Pleurotussajor-caju(Fr)Sjngers) Cultivation - PHOMLASABOUD, khantavanh; XAYXANADETH, VongPhet; SALITSAY, Timnoy (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
The objective of this study was to determine the most suitable type of manure for the growth and yield of Grey Oyster mushrooms and to evaluate their economic viability. The experiment was conducted at the mushroom cultivation house of the Department of Plant Science, Faculty of Agriculture and Forest Resources, Souphanouvong University, from December 20, 2021, to April 20, 2022 (a 4-month duration). The experimental design followed a Randomized Complete Block Design (RCBD) consisting of 4 treatments and 4 replications, with 40 bags per treatment. The treatments included: T1 (Control formula from Souphanouvong University), T2 (Poultry manure), T3 (Cattle manure), and T4 (Pig manure). The results indicated that all treatments showed statistically significant differences at a 95% confidence level(P < 0.05). Treatment T1 (Control) achieved the highest yield, with an average weight of 226.85 g/bag, 14.62 flowers/bag, a cap width of 6.12 cm, a stalk length of 5.23 cm, a stalk circumference of 3.19 cm, and an individual flower weight of 16.29 g. This was followed by T2, T3, and T4, respectively. However, from an economic perspective, T2 provided the highest economic return, yielding a marginal net benefit of 88,799 Kip per 50 bags. In conclusion, while the standard formula (T1) produced the highest biological yield due to its complete nutrient profile, the use of T2 as a supplement in Oyster mushroom cultivation is the most effective for increasing economic efficiency and profitability for producers.